PEMANFAATAN MEDIA GLOBE TERHADAP PEMAHAMAN KONSEP GARIS LINTANG DAN BUJUR PADA SISWA MENENGAH ATAS - Rizkykha Ayu Pradhita; Saptono Putro (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Geography is a discipline that fundamentally emphasizes the development of critical and analytical thinking skills among students through the integration of natural sciences, social sciences, and humanities. Through this research, the researcher aims to examine the extent to which globe media contributes to enhancing students' understanding of latitude and longitude concepts among 10th-grade students at SMA Teuku Umar Semarang. A quantitative approach utilizing a quasi-experimental design was selected as the methodology for this study, specifically implementing a non-equivalent control group design. Statistical testing was conducted in sequential stages, beginning with prerequisite tests including normality distribution tests and data homogeneity tests. Once both assumptions were satisfied, the procedure continued with comparative analysis using independent sample t-tests and N-Gain test analysis to measure the degree of improvement in students' conceptual understanding. The results of the data analysis demonstrate that the use of globe media has a significant impact on improving students' understanding of astronomical coordinate concepts. This effectiveness is clearly evidenced by the N-Gain score of the experimental group, which was classified as 'High' (0.79), significantly surpassing the control group, which achieved only a 'Medium' classification (0.65). Based on these findings, it can be concluded that the use of physical globe media has proven to be an effective tool for spatial visualization and understanding, serving a crucial role in helping students comprehend Earth's spatial concepts rather than functioning merely as a conventional visual aid. ABSTRAK Geografi ialah disiplin ilmu yang secara mendasar menekankan dalam menstimulasi kecakapan berpikir kritis sekaligus analitis para peserta didik lewat integrasi ilmu alam, ilmu sosial, hingga humaniora. Melalui penelitian ini, peneliti bermaksud untuk menguji sejauh mana kontribusi media Globe dalam memicu peningkatan pemahaman konsep garis lintang dan garis bujur pada siswa kelas X SMA Teuku Umar Semarang. Pendekatan kuantitatif dengan jenis eksperimen semu (quasi-experimental) dipilih sebagai metode dalam penelitian ini, di mana pelaksanaannya bertumpu pada rancangan non-equivalent control group design. Pengujian statistik dilakukan secara bertahap, diawali dengan pengujian prasyarat yang mencakup uji distribusi normalitas serta uji homogenitas data. Setelah kedua asumsi tersebut terpenuhi, prosedur dilanjutkan dengan melakukan analisis komparatif menggunakan independent sample t-test serta analisis uji N-Gain untuk mengukur tingkat peningkatan pemahaman konsep siswa. Hasil analisis data menunjukkan bahwa pemanfaatan media Globe memberikan pengaruh yang signifikan terhadap peningkatan pemahaman konsep koordinat astronomis siswa. Keberhasilan ini dibuktikan secara nyata oleh perolehan besaran nilai N-Gain kelompok eksperimen yang diklasifikasikan ke dalam kriteria 'Tinggi' (0,79), jauh melampaui kelas kontrol yang hanya berada pada kategori ‘Sedang’ (0,65). Berdasarkan temuan tersebut, dapat disimpulkan bahwa penggunaan media Globe fisik terbukti efektif bertindak sebagai alat bantu rekonstruksi spasial yang penting bagi siswa dalam memahami ruang bumi, bukan sekadar berfungsi sebagai alat peraga visual biasa.